Study on the Potential Use of Modified Tapioca Starch Sludge Waste for Volatile Fatty Acid Generation - Srivichai, Piyavadee; Rodsrida, Chumaporn; Chansamut, Nakit; Mueangchang, Wirinya (Trends in Sciences, 2022)
Starch sludge (SS) is a bulky main waste from modified tapioca starch production, a high potential substrate for alternative volatile fatty acids (VFA) production. Because it has relatively high organic content in SS is easy and fast to convert into VFA. However, there are limitations when fed overloading rate to anaerobic digestion (AD) system affecting the VFA production yield and system performance. This research aims to study the effect of initial feeding concentrations of SS between 0.5 and 2.5 % total volatile solids (TVS) on the VFA production efficiency by applying a batch continuously stirred tank reactor (CSTR) for digestion. The maximum VFA yield was 115 mg VFA/g TVS at a feeding rate of 2.0 % TVS of SS after 4 days of digestion. The digestion system could run under proper system performance and stability by showing higher pH. Besides, acetic acid was the predominant VFA intermediate indicating great effective digestion. Finally, the main bacteria in the inoculum were Arenimonas up to 33 % because it preferred to grow on glucose. And inoculum obtained from the beverage plant’s wastewater treatment system. These were so useful to select the inoculum for organic starch digestion.